Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Karyawan Pada Studio Renang Regional Bekasi - Winda Siregar; Bungaran Saing (GLOBAL SCIENTS PUBLISHER, 2026)
This study investigates the effects of work motivation and work discipline on employee performance, with employee satisfaction acting as a mediating variable at Studio Renang Regional Bekasi. The research employed a quantitative approach using an explanatory design, involving a sample of 75 employees selected through a saturated sampling technique. Data were processed using IBM SPSS 26, incorporating validity and reliability testing, classical assumption testing, multiple linear regression analysis, t‑tests, the F‑test, the Sobel mediation test, and the coefficient of determination (R²). The findings show that work motivation and work discipline each exert a positive and significant influence on employee satisfaction. In addition, work motivation, work discipline, and employee satisfaction positively and significantly affect employee performance. When examined simultaneously, these three variables significantly contribute to employee performance, as reflected in an Adjusted R² value of 54.3%. The Sobel test further confirms that employee satisfaction significantly mediates the relationship between work motivation and employee performance, as well as between work discipline and employee performance. These results suggest that enhancing employee performance requires not only strengthening motivation and discipline but also improving employee satisfaction as a key mechanism for fostering overall performance outcomes.